If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3e(3e + -10) = 2 Reorder the terms: 3e(-10 + 3e) = 2 (-10 * 3e + 3e * 3e) = 2 (-30e + 9e2) = 2 Solving -30e + 9e2 = 2 Solving for variable 'e'. Reorder the terms: -2 + -30e + 9e2 = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -30e + 9e2 = 0 Begin completing the square. Divide all terms by 9 the coefficient of the squared term: Divide each side by '9'. -0.2222222222 + -3.333333333e + e2 = 0 Move the constant term to the right: Add '0.2222222222' to each side of the equation. -0.2222222222 + -3.333333333e + 0.2222222222 + e2 = 0 + 0.2222222222 Reorder the terms: -0.2222222222 + 0.2222222222 + -3.333333333e + e2 = 0 + 0.2222222222 Combine like terms: -0.2222222222 + 0.2222222222 = 0.0000000000 0.0000000000 + -3.333333333e + e2 = 0 + 0.2222222222 -3.333333333e + e2 = 0 + 0.2222222222 Combine like terms: 0 + 0.2222222222 = 0.2222222222 -3.333333333e + e2 = 0.2222222222 The e term is -3.333333333e. Take half its coefficient (-1.666666667). Square it (2.777777779) and add it to both sides. Add '2.777777779' to each side of the equation. -3.333333333e + 2.777777779 + e2 = 0.2222222222 + 2.777777779 Reorder the terms: 2.777777779 + -3.333333333e + e2 = 0.2222222222 + 2.777777779 Combine like terms: 0.2222222222 + 2.777777779 = 3.0000000012 2.777777779 + -3.333333333e + e2 = 3.0000000012 Factor a perfect square on the left side: (e + -1.666666667)(e + -1.666666667) = 3.0000000012 Calculate the square root of the right side: 1.732050808 Break this problem into two subproblems by setting (e + -1.666666667) equal to 1.732050808 and -1.732050808.Subproblem 1
e + -1.666666667 = 1.732050808 Simplifying e + -1.666666667 = 1.732050808 Reorder the terms: -1.666666667 + e = 1.732050808 Solving -1.666666667 + e = 1.732050808 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '1.666666667' to each side of the equation. -1.666666667 + 1.666666667 + e = 1.732050808 + 1.666666667 Combine like terms: -1.666666667 + 1.666666667 = 0.000000000 0.000000000 + e = 1.732050808 + 1.666666667 e = 1.732050808 + 1.666666667 Combine like terms: 1.732050808 + 1.666666667 = 3.398717475 e = 3.398717475 Simplifying e = 3.398717475Subproblem 2
e + -1.666666667 = -1.732050808 Simplifying e + -1.666666667 = -1.732050808 Reorder the terms: -1.666666667 + e = -1.732050808 Solving -1.666666667 + e = -1.732050808 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '1.666666667' to each side of the equation. -1.666666667 + 1.666666667 + e = -1.732050808 + 1.666666667 Combine like terms: -1.666666667 + 1.666666667 = 0.000000000 0.000000000 + e = -1.732050808 + 1.666666667 e = -1.732050808 + 1.666666667 Combine like terms: -1.732050808 + 1.666666667 = -0.065384141 e = -0.065384141 Simplifying e = -0.065384141Solution
The solution to the problem is based on the solutions from the subproblems. e = {3.398717475, -0.065384141}
| 9x(x+2y+3z)= | | 6s^3+23s^2+33s=13s | | 3x-5=5+3x | | y+x^2-2x=0 | | x+y^2-2y=0 | | 10y+5x=100 | | 4y-24-9y+31= | | -4(y-3)=6y-38 | | f(-2)=-2+2(-2-1) | | -9x+-18+25=-38 | | 3+(-22)= | | 7-11x=x-33 | | 3log(7)(4)-5log(7)(m)= | | f(3)=3+2(3-1) | | -2x-10=44+8x | | 5t-2t=t | | 2z^2+7x=0 | | -4(2-y)+3y=4(y-4) | | (2x+4)(x-3)=0 | | f(-2)=-3(4-2)+2 | | 2x-3=4y+6 | | 4x^2-6x+5=x+1 | | 210x+100-72x^2=0 | | -9+4-(-5)= | | 8-3a^3=0 | | f(3)=-3(4-3)+2 | | X-6+2x=48 | | 64=-3(1-2n) | | 2x^2+28x+74=0 | | -65=136 | | 9z^2-26z-3=0 | | 18-7x=5(3x-2)+6 |